Superoxide dismutase and catalase activities in the seminal plasma of normozoospermic and asthenozoospermic beagles - Kawakami, E.(Nippon Veterinary and Life Science Univ., Musashino, Tokyo (Japan). Faculty of Veterinary Medicine); Takemura, A; Sakuma, M; Takano, M; Hirano, T; Hori, T; Tsutsui, T (Journal of Veterinary Medical Science, 2007)
We measured the blood plasma testosterone (T) levels and superoxide dismutase (SOD) and catalase activities in the seminal plasma of the ejaculates of 5 normal (2-5 years old) and 5 asthenozoospermic (AZ-) (3-5 years old) beagles. Sperm ejaculated by AZ-dogs was incubated for 3 hr in Eagle's MEM only (controls) or Eagle's MEM containing 100 units/ml of SOD or catalase. Sperm motility was examined during incubation. The mean (+- SE) plasma T level of the AZ-dogs (1.2 +- 0.2 ng/ml) was significantly lower than in the normal dogs (2.5 +- 0.2 ng/ml) (P0.005). The mean (+- SE) seminal plasma SOD and catalase activities (18.8 +- 1.9 and 0.5 +- 0.1 unit/g protein, respectively) were significantly lower in the AZ-dogs than in the normal dog (43.3 +- 2.5 and 2.2 +- 0.4 unit/g protein, respectively) (P0.001 and 0.01, respectively). The motility of sperm incubated in Eagle's MEM containing SOD or catalase was significantly higher than that of control sperm incubated in only Eagle's MEM after 2 or 3 hr of incubation (P0.05). The results of this study indicate that poor T secretion by the testes and low antioxidant enzyme activities are related to AZ in the dog.